2017
DOI: 10.1002/pssa.201600471
|View full text |Cite
|
Sign up to set email alerts
|

Recurring polyhedral motifs in the amorphous indium gallium zinc oxide network

Abstract: The coordination polyhedra around the cations are the building blocks of ionic solids. For amorphous InGaZn oxide (a‐IGZO), these coordination polyhedra are identified to investigate properties that depend on short range interactions. Therefore, in this first principles based study, a large number (10) of samples of a‐IGZO were prepared by ab initio melt‐and‐quench molecular dynamics, so that several distinct samples of the amorphous landscape are obtained corresponding to local minima in energy. Based on a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The representative pseudo-band structures (a-d) and the corresponding orbital-resolved partial electronic density of states (PDOS) (e-h), for the two compositions of a-ZnON and a-IGZO, are shown in Fig.2. All amorphous structures were generated in the same way as discussed earlier, except for a-IGZO-2217* (2217 represents the atomic ratios of In, Ga , Zn and O) structure, which was obtained from the previous work of Divya et al 47 . a-IGZO-1114 (1114 represents the atomic ratio of In, Ga, Zn and O) structures were taken from our previous work 40 and all the structures have densities in the range of 85%-91% of the theoretical densities of their crystalline counterparts.…”
Section: Electronic Structure Of A-znon and A-igzomentioning
confidence: 99%
“…The representative pseudo-band structures (a-d) and the corresponding orbital-resolved partial electronic density of states (PDOS) (e-h), for the two compositions of a-ZnON and a-IGZO, are shown in Fig.2. All amorphous structures were generated in the same way as discussed earlier, except for a-IGZO-2217* (2217 represents the atomic ratios of In, Ga , Zn and O) structure, which was obtained from the previous work of Divya et al 47 . a-IGZO-1114 (1114 represents the atomic ratio of In, Ga, Zn and O) structures were taken from our previous work 40 and all the structures have densities in the range of 85%-91% of the theoretical densities of their crystalline counterparts.…”
Section: Electronic Structure Of A-znon and A-igzomentioning
confidence: 99%
“…Several studies have already been conducted using this approach, providing valuable insights into the material’s properties. For example, Nomura et al demonstrated the structural similarities between a-IGZO and its crystalline counterpart (c-IGZO) using ab initio simulations and X-ray absorption fine structure analysis . Walsh et al went further by comparing the coordination structures of a-IGZO with those of other conducting oxides, and Divya et al suggested a new method to determine the polyhedral motifs within a-IGZO beyond simple distance cutoffs between oxygen and metal atoms. , However, there remain limitations to the prior works, particularly in terms of computational expense and the difficulty of obtaining sufficient sampling for statistical analysis. As a result, much of the current focus in structural analysis of a-IGZO has centered on metal-centered complex structures, which are complex polyhedra with a metal atom at the center and comparatively easier to sample due to their simple coordination environment.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous metal oxide films exhibit a range of attractive properties for technological applications and are candidate materials for next-generation thin-film devices, such as thin-film transistors. In particular, amorphous semiconducting oxides such as Zn–O, In–O, amorphous In–Ga–O, amorphous In–Ga–Zn–O, amorphous In–Sn–O, amorphous Zn–In–Sn–O, and amorphous Zn–Sn–O have garnered significant interest. ,,, Such materials have been shown to have high electron mobilities, , tunable conductivity, high optical transparency, , mechanical stress tolerance, ,, and compatibility with organic dielectric and photoactive materials, making them applicable for a number of applications. ,, The performance of these materials is strongly correlated with the structure and disorder of the material. , However, the inherent complexity of amorphous oxide structures has hindered our understanding of chemical transformations and their influence on structure–property relationships.…”
Section: Introductionmentioning
confidence: 99%